The Mediating Role of Work Motivation in Linking Leadership, Rewards, and Sales Performance at Astra Motor - Nur Ikhsanida, Zhackya; Heriyadi, Heriyadi; Endah Mayasari; Maria Christiana Iman Kalis; Rizani Ramadhan (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze the influence of transformational leadership and rewards on employee performance, with work motivation as a mediating variable, among contract salespeople at PT Astra International Tbk – Honda Sales Operation, Pontianak Patimura Branch. A quantitative approach was used, with data analyzed using Partial Least Squares (PLS) through SmartPLS 4. The results show that transformational leadership and rewards have a significant effect on work motivation and employee performance. Work motivation also significantly influences performance and mediates the relationship between transformational leadership and rewards on performance. This study highlights the importance of inspirational leadership styles and fair reward systems in enhancing the motivation and performance of contract sales employees.